PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA HOTEL ASTON KUPANG & COVENTION CENTER - Saragi, Rulli (Jurusan Pariwisata Politeknik Negeri Kupang, 2019)
The title of this research is â€œ The influence of compensation and motivation on employee performance at on Hotel Aston Kupang & Covention Centerâ€. The main problem formulation in this research how competation, motivation effect on employee performance at on Hotel Aston Kupang & Covention Center. The purpose of this research is to answer the problem to know how to compensate and motivation effect on employee performance at On Hotel Aston Kupang & Covention Center and to find out whether compencation, motivation partiali and simultaneously effect of employee performes at Hotel Aston Kupang & Covention Center. The result show that show that competation, motivation effect and employee performance on Hotel Aston Kupang & Covention Center on goodness category and there compentation, motivation, and employee performance effect as partiali and simultaneously.